Agroeconomic evaluation of food production in conversion systems to organic farming in Orizona, Goias State, Brazil. - SILVA, O. F. da (2018)
The study proposes to describe two profiles of producers, evidently different in their production base, to guide actions of technology transfer, respecting the way of making of these producers, bringing them to the base of scientific knowledge, with some agricultural and management practices to increase food production through the sustainable use of available resources, such as the conservation of soil, water and biodiversity.